2020
DOI: 10.3390/catal10020158
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Performance of Bulk and Al2O3-Supported Molybdenum Oxide for the Production of Biodiesel from Oil with High Free Fatty Acids Content

Abstract: Non-edible vegetable oils are characterized by high contents of free fatty acids (FFAs) that prevent from using the conventional basic catalysts for the production of biodiesel. In this work, solid acid catalysts are used for the simultaneous esterification and transesterification with methanol of the FFAs and triglycerides contained in sunflower oil acidified with oleic acid. Molybdenum oxide (MoO 3 ), which has been seldom considered as a catalyst for the production of biodiesel, was used in bulk and alumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 40 publications
1
24
0
1
Order By: Relevance
“…This class of catalysts includes, among others, inorganic oxides [19] , enzymes [20] , ion exchange resins [21] and zeolites [22] . However, a high catalytic performance has been exhibited by copper oxide [23] and molybdenum oxide [24] in the transesterification of vegetable oils. Also, they are easily synthesized by conventional and low-cost methods, which reinforces the interest in these compounds [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%
“…This class of catalysts includes, among others, inorganic oxides [19] , enzymes [20] , ion exchange resins [21] and zeolites [22] . However, a high catalytic performance has been exhibited by copper oxide [23] and molybdenum oxide [24] in the transesterification of vegetable oils. Also, they are easily synthesized by conventional and low-cost methods, which reinforces the interest in these compounds [25] , [26] .…”
Section: Introductionmentioning
confidence: 99%
“…The modified Mo catalyst with the weak acid content Moreover, in more detail on the NH3-TPD analysis, apart from the number of catalyst acid sites, the ability of the modified Mo oxide catalyst in adsorbing and desorbing substrate molecules (base species) from the surface greatly supports the performance of heterogeneous catalysts, where the ability of the active site of the catalyst to adsorb-desorb substrates and products is one of the important factors. Furthermore, the Navajas et al also reported that the Molybdenum oxides have interesting activity regarding the active sites as the Lewis acid and the Brönsted acid in the conversion of vegetable oil [52]. Considering the Lewis acidity, the molybdenum species could provide the orbital d and can form the reactive transition state with the substrate and lead the lower energy pathway in the reaction.…”
Section: Correlation Of Physicochemical Properties Of Catalysts and T...mentioning
confidence: 99%
“…It is evident that the incorporation of the oxide phases of Ni, Mo and the binder into the HAlMCM-41 material generates a significant increase in the number of acid sites. The electron-deficient species from active-phase components may serve as a kind of newly created Lewis acid site, which recompenses the primary Lewis acidity originating from the parent HAlMCM-41 and being overlapped during impregnation [43,44]. The relatively high Lewis acid site concentrations in the NiMo/HAlMCM-41 can be also ascribed to the presence of the alumina binder (γ-Al 2 O 3 ).…”
Section: Acidity By Py-irmentioning
confidence: 99%